Increasing the cyclic strength of threaded joints through the unloading of cracked sections - Krenevičius A.; Kačianauskas R.; Leonavičius M.; Hui D.; Feo L. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The cyclic strength of the axially loaded threaded joints is considered and the procedural method to increase their lifetime through the unloading of cracked sections is presented. The method operates by varying the mutual positions of the stud and the nut. It was shown how to exploit resources of the threaded joint after opening of the crack without reduction of the safety. The developed mathematical model allows control the accumulation of the fatigue damage as well as the crack growth in the roots of the stud thread. Increase of the cyclic lifetime is theoretically evaluated by the ratio of the numbers of loading cycles required to initiate cracks in the roots of unengaged and the most dangerous engaged turns of the stud. Performance of the elaborated technique is demonstrated by considering the crack growth in depth of the nut. The relative safety of the unloaded cross-sections containing cracks is studied. Comparison of the presented developments with standard safety requirements is presented.